Estudo dos mecanismos envolvidos nas alterações cardíacas em um modelo murino de dengue (DENV-3) - Lucas Miranda Kangussu Gomes Oliveira (2012)
The dengue virus, which belongs to the Flavivirus genus within the Flaviviridae family, has been classified into four serotypes, DENV 1-4, which are genetically and antigenically different. Nowadays, dengue disease is the major arbovirosis that affects human beings; moreover, it is the most widespread viral infection in urban tropical and sub-tropical areas, constituting an important world health problem. In addition, there is no effective treatment or vaccines available for the prevention of this disease. These factors are associated with a poor understanding of the pathogenesis of the disease due to the lack of animal models that mimic the infection seen in humans. Thus, the purpose of this study was to identify whether there are cardiac abnormalities in a murine model of dengue (DENV-3) and to characterize the mechanisms involved in these changes. Initially, a murine model of infection induced by a clinical isolate of the serotype 3 viruses (DENV-3) was characterized in BALB/c mice. The serotype-3 of Dengue virus adapted to mice was effective in inducing infection and mimicking the signs and symptoms observed in severe illness in humans and thus, represents a murine model for the study of the pathogenesis of this disease. Dengue virus-infected mice lost weight and succumbed to the infection in an inoculum-dependent manner. Significant hematologic changes, detectable viral load in target organs and blood, liver damage and bleeding in the lungs and gut tissue were also observed. It is known that the development of systemic inflammatory responses to uncontrolled virosis is the cause of significant morbidity / mortality associated with infection. In our experimental model, the systemic inflammatory response was characterized by increased vascular permeability, recruitment and activation of leukocytes and markedly production of pro-inflammatory cytokines and chemokines. There was also a significant reduction in blood pressure, increased heart rate, dramatic increase in vascular permeability and hypovolemia, suggesting that infected mice had hypovolemic shock. Viral load was detected in the heart of infected animals, as well as leukocyte infiltration and production of cytokines (TNF-, IL-6, IL-1 and IL-17) and chemokines (CXCL1/KC, CCL2/MCP-1). The infection with DENV-3 triggered pericarditis, myocarditis and oxidative stress, leading to electrophysiological changes in cardiomyocytes which culminated in cardiac dysfunction. Based on these results we may suggest that the heart is an important target of infection by Dengue virus, suffering intense inflammation, oxidative stress and electrophysiological changes that culminate in cardiac dysfunction.